Drip irrigation scheduling of Mango cv. Langra under subtropical condition of Uttar Pradesh - BHRIGUVANSHI, S. R.; ADAK, TARUN; KUMAR, KAILASH; SINGH, V. K.; SINGH, VINOD KUMAR; SINGH, ACHAL (Journal of Soil and Water Conservation, 2021)
Drip irrigation scheduling is an important water management strategy in fruit crops wherein full water requirement of the crop is applied over its entire phenological stages based on evaporation replenishments. Keeping this in view, a field experiment was laid out under subtropical environment to evaluate the effect of phenology based irrigation scheduling on yield and water use efficiency of mango cultivar Langra for 4 years in a 20 years old orchards near Lucknow. Irrigation scheduling consisted of open pan evaporation (OPE) replenishments (90, 70 and 60% of OPE) under drip irrigation system and basin irrigation as control in association with three nitrogen levels (75 and 50% of the recommended dose of nitrogen and no fertigation as control). Drip irrigation irrespective of fertigation significantly increased fruit yield and water use efficiency over traditional basin irrigation. The percent increase in fruit yield over basin irrigation system was 12.2, 42.5 and 47.9% as compared to 0.90, 0.70 and 0.60 OPE respectively. The per cent yield improvement in 0.60 OPE was higher as compared to 0.90 and 0.70 OPE and it was around 31.6 and 36.1% respectively. The water use efficiency ranged between 5.25-9.94 kg fruits per m3 of water applied in the drip irrigation system as compared to 3.69 kg fruits per m3 of water applied in basin application of irrigation. Moreover, the per cent of irrigation water saved was quantified and it was found that the drip irrigation had saved 21.13, 35.40 and 45.20% irrigation water in 0.90, 0.70 and 0.60 OPE respectively over its basin application.